Spatial memory and hippocampal enhancement. (August 2015) - Peters, Marco; Muñoz-López, Mónica; Morris, Richard GM
Highlights: Enhancement of spatial memory may affect encoding, consolidation or retrieval. Interventions that successfully enhance in one processing domain may inhibit in another. Enhancement of spatial memory includes extending the persistence of memory over time. Abstract : Given the central role of hippocampal function in spatial and episodic memory, the concept of enhancing it when compromised is attractive. This might be realised behaviourally, pharmacologically or via more radical routes such as brain stimulation. Successful approaches in each of these domains include trial-spacing, rest, and NMDA or cholinergic receptor modulation, but the goal of enhancement has to be clear as some approaches can enhance in one domain but inhibit in another. Enhancement may also extend the duration of memory rather than augment encoding, an idea conceptually embedded into the synaptic-tagging-and-capture theory of memory persistence. In addition, recent work on human spatial memory reflects new findings about the interacting components of egocentric and allocentric processing of human navigation.